Biosynthesis of beauvericin and enniatins invitro by wheat Fusarium species and natural grain contamination in an area of central Italy - Covarelli, Lorenzo; Beccari, G.; Prodi, A.; Generotti, S.; Etruschi, F.; Meca, G.; Juan, C.; Mañes, J. (N R C Research Press, 2015)
© 2014 Elsevier Ltd. Contamination of wheat grain by beauvericin (BEA) and enniatins (ENs) is a global emerging mycotoxicological food problem. In this study, strains of Fusarium avenaceum (FA), Fusarium poae (FP), Fusarium equiseti and Fusarium sporotrichioides, all potential BEA and EN producers, isolated from 162 grain samples of durum and soft wheat harvested in 2009 and 2010 collected in an area of central Italy, were preliminarily screened for the presence of the esyn1 gene, encoding the multifunctional enzyme enniatin-synthetase for the detection of potential hexadepsipeptide-producing isolates. All positive isolates were tested for their ability to biosynthesize BEA and ENs invitro. In addition, all wheat samples were investigated for the natural presence of BEA and ENs (ENA, ENA1, ENB, ENB1). All FA and FP strains resulted to be positive for the presence of the esyn1 gene. All FA strains showed the ability to biosynthesize ENs invitro but not BEA. Conversely, all FP strains resulted to be BEA producers and some of them co-biosynthesized ENs. A remarkable presence of "emerging" mycotoxins was found in the grains, particularly ENs. Co-contamination by BEA and ENs also occurred. This study gives an important contribution to assess the risk posed by mycotoxigenic fungi and their mycotoxins in food.